Perhitungan SCF Untuk Analisa Fatigue pada Sambungan Struktur Anjungan Lepas Pantai - Tawekal, Ricky L. (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Fatigue is one of the failure modes on offshore structures that need to be monitored carefully. Fatigue analysis is usually carried out to predict the service life of structure due to fatigue on its joints. Fatigue damage is also depent on Stress Concentration Factor (SCF). SCF is the ratio of hotspot stress at joint to nominal stress on member. Hotspot stress is extreme stress occur at intersection of the joint. In this paper, the calculation of SCF at joint T is carried out by using Finite Element Method that available in ProEngineer Software.Â  The resulted SCF based on Finite Element Method will be compared to calculated SCF based on empirical formula. In addition, SCF on joint T will also be compared to SCF on joint with tubular stiffener.Keywords: fatigue, failure mode, offshore structures, stress concentration factorPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3910[How to cite: Tawekal, R.L., 2005, Perhitungan SCF Untuk Analisa Fatigue pada Sambungan Struktur Anjungan Lepas Pantai, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 63-74]